Entropy Analysis of a Radiating Variable Viscosity EG/Ag Nanofluid Flow in Microchannels with Buoyancy Force and Convective Cooling - Monaledi, R.L.; Makinde, Oluwole Daniel (Diffusion and defect data. Solid state data. Pt. A, Defect and diffusion forum, 2018)
The inherent irreversibility of a variable viscosity ethylene glycol/silver (EG/Ag) nanofluid single-phase Poiseuille flow in a vertical microchannel with convective cooling under the combined influence of buoyancy force, nonlinear thermal radiation, nanoparticles shape and volume fraction is investigated. The nonlinear model equations are obtained and numerically solved via shooting method with Runge-Kutta-Fehlberg integration scheme. Pertinent results with respect to the effects of emerging thermophysical parameters on the nanofluid velocity, temperature, skin friction, Nusselt number, thermal stability criteria, entropy generation rate and Bejan number are presented graphically and discussed. It is observed that thermal radiation, Biot number and buoyancy force boost the release of heat energy thereby cooling the flow system. Meanwhile, an increase in nanoparticles volume fraction lessens the entropy generation rate which augment the exergetic effectiveness and thermal stability of the flow system.